Pengaruh Fasilitas Dan Pelayanan Terhadap Kepuasan Pengunjung Di Pantai Bali Lestari - Sri Riski Handayani; Edi Winata (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there is an effect of facilities and services on visitor satisfaction at Bali Lestari Beach. The sample of this study was 86 people, sampling using incidental sampling, namely determining the sample who happened to meet. Data analysis used multiple regression test, while data processing used SPSS. The results showed that partially the facilities variable had a positive and significant effect on visitor satisfaction, and partially service variables had a positive and significant effect on visitor satisfaction, while simultaneously facilities and services had a positive and significant effect on visitor satisfaction at Bali Lestari Beach.